Fundacje, media, etyka. Ciąg dalszy rozważań - Rotengruber, Przemysław (Annales. Etyka w Życiu Gospodarczym, 2008)
The object of my last year’s presentation were communication (ethical, integration, political)threats posed by a foundation seen as an extension to a company in its traditional sense. I came tothe conclusion that an automatic transfer of social trust capital to the parent company (in certain,specified by me, contexts) causes the foundation to betray its mission. It is the company that becomesthe main beneficiary of mutual aid activities.This year, the paper addresses the following three issues. Firstly, I intend to show the symbolicpressure exerted on both consumers and producers, which is made possible by the ‘labeling’ of productsof ‘socially sensitive’ companies. There would be no point questioning the fact of shaping socialattitudes if it weren’t for an ambiguous position of the co-ordinator of the enterprise, who becomes vestedwith the rights of a certification authority.Another question under consideration is the transformation of a foundation into a quasi-company.A third-sector organization adds business activity to the goals specified in its by-laws. It resultsin taking on highly-skilled professionals who have nothing to do with charitable activity of a thirdsector organization.Finally, there is a danger of a foundation’s approximation to a second-sector organization.A foundation may be financed by a public administration body. This may lead to the division ofthe final product of a foundation between the beneficiaries and the body which sponsors its operationusing a ‘lump sum’ payment.Whichever the problem, the key aspect seems societal control over mutual aid activities. Its lackresults in an abuse of power and the diminished trust of the manipulated society in effective cooperation.